SPECIAL ASPECTS OF OBJECT’S VIBRATION OF PIPELINE SYSTEM OF OIL AND GAS PRODUCTION FIELDS - Іващенко, Василь Трифонович; Слободян, Володимир Іванович; Лях, Михайло Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Dynamic characteristics of the objects of pipeline systems of oil and gas production fields and the operation modes of initiation of vibration in systems with lumped parameters such as machines and pipeline fittings and supporters and in systems with distributed parameters such as linear parts of pipelines, columns and beams of construction are observed. It’s figured out that fluctuation of the objects is determined by excitation characteristics such as spectral content of excitation force and frequency characteristics of system.